2014
DOI: 10.9790/7388-04543340
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Application of Augmented Reality Technology in Early Childhood Classroom in Malaysia

Abstract: The purpose of this study is to observe the familiarity of the AR application especially its implementation in a learning environment, and to determine the effectiveness of AR application in the classroom. The use of Augmented Reality (AR) in the classroom has the potential to enhance the traditional learning method. This study uses AR technology to implement an AR-learning environment for preschool children. Although previous studies have indicated that the AR technology enhances learning effectiveness, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 16 publications
0
29
0
8
Order By: Relevance
“…Based on previous evaluation results, AR with multimedia based learning was able to provide engaging (Pribeanu, 2014;Abhishek et al, 2013;Dunser et al, 2012;Rambli et al, 2012;Abas et al, 2011), enjoyment (Pribeanu, 2014;Cai et al, 2014;Ibanez et al, 2014;Abhishek et al, 2013) and fun (Rasalingam et al, 2014;Rambli et al, 2013;Yusoff et al, 2010;McKenzie and Darnell, 2003) in enhancing the motivation. However, in this study, ease of use is not significantly related to motivation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Based on previous evaluation results, AR with multimedia based learning was able to provide engaging (Pribeanu, 2014;Abhishek et al, 2013;Dunser et al, 2012;Rambli et al, 2012;Abas et al, 2011), enjoyment (Pribeanu, 2014;Cai et al, 2014;Ibanez et al, 2014;Abhishek et al, 2013) and fun (Rasalingam et al, 2014;Rambli et al, 2013;Yusoff et al, 2010;McKenzie and Darnell, 2003) in enhancing the motivation. However, in this study, ease of use is not significantly related to motivation.…”
Section: Discussionmentioning
confidence: 94%
“…The feeling of fun enhances the ability of understanding and knowledge retention (Rambli et al, 2013). Several previous studies have proven that AR is fun to use in the learning process (Rasalingam et al, 2014;Rambli et al, 2013;Yusoff et al, 2010;McKenzie and Darnell, 2003). …”
Section: Measurementsmentioning
confidence: 98%
See 1 more Smart Citation
“…Penggunaan Augmented Reality yang ditujukan kepada anak usia dini telah dikembangkan oleh beberapa peneliti diantaranya adalah penelitian yang dilakukan oleh Rasslenda-Rass [11] yang menghasilkan tingkat ketertarikan dan motivasi anak menggunakan augmented reality dibandingkan pembelajaran secara konvensional. Penelitian ini menghasilkan AR Flashcard yang didesain untuk aplikasi iOS.…”
Section: Augmented Reality Dan Anak Usia Diniunclassified
“…Based on observatory studies conducted on existing educational AR applications, researchers have identified increased motivation, active engagement, "improved perceived enjoyment", increased accessibility and variety of education content, complements active learning, "greater opportunities for collaboration", improved capacity to retain information, facilitates understanding of the subject or topic, rendering concrete manifestations of abstract concepts, "provides powerful contextual, on-site learning" as benefits of using AR [4] [15]. AR has been implied to be successful especially in engaging learners in learning a particular topic, subject or concept.…”
Section: • Skills Trainingmentioning
confidence: 99%